Mobilising knowledge with nurses practicing during the Covid-19 pandemic: Prioritising strategies for enhancing nurses’ psychological wellbeing in the workplace - E. Rowland; A. Conolly; R. Abrams; R. Harris; J. Maben (Wellbeing, Space and Society)
The Covid-19 pandemic exacerbated pressures on an already strained nursing workforce, heightening poor psychological and emotional wellbeing. A two-year qualitative longitudinal study with nurses (n = 50) examined these impacts. Following study completion, efforts focused on mobilising knowledge through the development strategies (outputs) to better support nurses’ psychological wellbeing during future pandemics and inform healthcare policy (outcome) that over time, could potentially lead to real-world impact from our research.In healthcare, demonstrating research impact is important yet complex. Knowledge mobilisation activities are crucial for developing impact pathways by collaborating with key stakeholders to share knowledges and find solutions to workplace challenges. This paper documents the early stages of our impact journey, where a subsample of nurses (n = 10) participated in a workshop designed to mobilise knowledge through reflective discussions that would prioritise strategies to enhance nurses’ psychological wellbeing.The workshop included four knowledge mobilisation activities: a film preview, sharing biographical objects, a world ‘strategy’ café, and a celebratory event. The film resonated with nurses, uniting them through a collective narrative while biographical objects enriched reflective discussions by focussing on personal lived experiences. The world ‘strategy’ café activity was effective in facilitating reflective discussions which prioritised workplace strategies that could inform health care guidance and policy. The celebratory event allowed nurses to reflect on their participation in both the study and the workshop and indicated that knowledge mobilisation activities can demonstrate ‘soft’ impact from the study. When considering research impact, researchers could be more attentive to soft impact as one facet of knowledge mobilisation.